Determination of Nitrite and Nitrate Level in Wastewater Discharge from Smoked Fish Industry - Wina Yulianti; Ima Kusumanti; Nurul Jannah (JURNAL SAINS NATURAL, 2022)
This research aimed to determine nitrite and nitrate contamination in wastewater discharge from the smoked fish industry around the fishpond area in Penatarsewu village, Sidoarjo East Java. Samples were taken from ten locations along The Alo River from September to November 2020. Nitrate and nitrite levels were determined by the Standard Method for Examination of Water and Wastewater 4500-NO2-B dan 4500-NO3-B. Nitrite formed a reddishpurple azo dye produced by coupling diazotized sulfanilamide with N-(1-naphthyl)-ethylene-diamine dihydrochloride after a visible spectrophotometer measured the complexes nitrite at wavelength 543 nm. Meanwhile, the Nitrate level was determined by ultraviolet spectrophotometer at a wavelength of 220 nm. The standard nitrite calibration curve was shown by the line equation y= 3,30361x-0,0028 and a determination coefficient of 0.9999. Whereas the standard nitrate was showed by the line equation y=0,2507x + 0,0067 and a determination coefficient 0,9996. The level of nitrate and nitrite in the sample ranged from 0.05-0.93mg / L 1,2-1,6 mg / L. According to a quality standard threshold value for nitrite and nitrate-based on the Government Regulation of the Republic of Indonesia (PPRI) No.82 2001 is 0,06mg/L and 10 mg/L, therefore it can be concluded that some samples are above the threshold value for nitrite level.Keywords: Alo River,  nitate,  nitrite,  smoked fish,  spectrophotometerPenentuan Kadar Nitrit dan Nitrat Pembuangan Limbah Cair Industri Ikan AsapABSTRAKPenelitian bertujuan untuk menentukan tingkat kontaminasi nitrat dan nitrit pada limbah industri ikan asap di sekitar kawasan tambak ikan asap di Desa Penatarsewu, Sidoardjo, Jawa Timur. Sampel diambil dari 10 titik  di areal sekitar tambak sepanjang badan Sungai Alo pada bulan September sampai November 2020. Penentuan kadar nitrat dan nitrit mengacu pada Standard Methods for the Examination Water and Wastewater 4500-NO2-B dan 4500-NO3-B. Nitrit membentuk kompleks ungu kemerahan yang dihasilkan dari kopling sulfanilamida dengan N-(1-naptil)-etilena-diamina dihidroklorida kemudian kadarnya ditentukan dengan spektrofotometer sinar tampak pada panjang gelombang 543 nm. Kadar nitrat ditentukan menggunakan spektrofotometer ultraviolet pada panjang gelombang 220 nm. Hasil pengukuran standar nitrit menghasilkan persamaan garis y=3,30361x-0,0028 dengan koefesien determinasi 0,999 dan standar nitrat menghasilkan persamaan garis y=0,2507x+0,0067 dengan koefesien determinasi 0,9996. Kadar nitrit dan nitrat secara berturut-turut berkisar antara 0,05-0,93 mg/L dan 1,2-1,6 mg/L. Berdasarkan nilai ambang batas baku mutu nitrit dan nitrat berdasarkan Peraturan Pemerintah Republik Indonesia (PPRI) No.82 tahun 2001 adalah 0,06 mg/L dan 10 mg/L, maka dapat disimpulkan bahwa beberapa sampel mengandung kadar nitrit  di atas ambang batas.Kata kunci : ikan asap, nitrat, nitrit, Sungai Alo, spektrofotometer